New Technologies for Human Rights Law and Practice - Land, Molly K.; Aronson, Jay D. (Social Sciences, 2018)
This book is for human rights scholars and practitioners who are interested in the practical and conceptual impact of technology on their advocacy, research, and practice. It provides an explanation of the major risks and opportunities in this domain, suggests questions and issues to be considered, and offers practical strategies for navigating this complex terrain. This title is also available as Open Access.